Stability of the RC Column under Horizontal Impacts - A. V. Alekseytsev (Железобетонные конструкции)
Approaches to assessment of stability of reinforced concrete columns in case of horizontal emergency impact have been investigated. For this purpose, finite-element modeling of the system in spatial formulation, calculation according to the deformed scheme in the scope of nonlinear static analysis and dynamic transient process have been implemented. When constructing the model, the hexahedral elements were used, working in accordance with the Drucker-Prager model for concrete, and the rebars deformed according to the Prandtl model were used to modelling the reinforcement.The impact action was considered as a short-term pulse of constant intensity. Dependence diagrams for critical force on various scenarios of emergency impacts on the column have been obtained. Results of researches can be used for an estimation of resistance to the progressive collapse of reinforced concrete structures at their variants design and optimization.